#NotTheSame: Asian American subgroups moderate the relation between campus racial climate and perceived burdensomeness during the COVID-19 pandemic - Jin, Joel; Zhou, Vanessa; Taone, Trevor; Ichimura, Emi (Frontiers in Public Health, 2023)
The present study examined the effect of campus racial climate on perceived burdensomeness, a suicide risk factor, among Asian American college students during the COVID-19 pandemic, when anti-Asian racism was present. To disaggregate these data, there was a test of whether Asian American ethnicity subgroup identification as Southeast and South or East Asian changed the association between campus racial climate on perceived burdensomeness. The current sample included 148 college students, 73 Southeast or South Asian Americans, and 75 East Asian American. The study participants were enrolled at a small liberal arts institution located in the Pacific Northwest region of the United States. Researchers collected data across 3 days (9–12 April 2020) via an online questionnaire. Both groups reported similar levels of campus racial climate and perceived burdensomeness. Bivariate correlations indicated that campus racial climate was positively correlated with perceived burdensomeness for Southeast and South Asians only. Moderation analyses revealed that a negative campus racial climate was related to greater perceived burdensomeness among Southeast and South Asian, but not East Asian, American students. This finding supports the need for disaggregation of Asian subgroups in mental health research to understand the diverse experiences within the Asian American community. Furthermore, there is a need for higher education institutions to consider tailoring interventions and tools that fit into the unique cultural and sociohistorical experiences of ethnic and racial subgroups among Asian American students.